2020
DOI: 10.2147/cmar.s218756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management of Immune Checkpoint Inhibitor Toxicities</p>

Abstract: Immune checkpoint inhibitors (ICIs) have radically changed the clinical outcome of several cancers with durable responses. CTLA-4 (cytotoxic T lymphocyte antigen-4), PD-1 (programmed cell death protein 1) or PDL-1 (programmed cell death ligand protein 1) represent ICIs that can be used as monotherapy or in combination with other agents. The toxicity p\rofiles of ICIs differ from the side effects of cytotoxic agents and come with new toxicities like immune-related adverse events. Typically, these toxicities occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 105 publications
(244 reference statements)
0
20
0
Order By: Relevance
“…Although moist rales/crackles are not very commonly manifested symptoms in the patients with immune checkpoint inhibitor-related pneumonitis, they has been listed as one of the clinical findings suspecting the onset of severe pneumonitis recommending a chest CT (21,22). Furthermore, we demonstrated that in NSCLC patients, the incidence of symptomatic pneumonitis induced by atezolizumab plus chemotherapy was lower in the group also treated with bevacizumab than in the group without bevacizumab.…”
Section: Discussionmentioning
confidence: 63%
“…Although moist rales/crackles are not very commonly manifested symptoms in the patients with immune checkpoint inhibitor-related pneumonitis, they has been listed as one of the clinical findings suspecting the onset of severe pneumonitis recommending a chest CT (21,22). Furthermore, we demonstrated that in NSCLC patients, the incidence of symptomatic pneumonitis induced by atezolizumab plus chemotherapy was lower in the group also treated with bevacizumab than in the group without bevacizumab.…”
Section: Discussionmentioning
confidence: 63%
“…The majority of toxicities caused by ICIs are low in severity, but some are more serious and require multidisciplinary management of side effects. To reduce the risk of experiencing severe toxicities, gathering information on different immune toxicities has been necessary and treatment practices have needed to adapt quickly [3,5] .…”
Section: Discussionmentioning
confidence: 99%
“…When examining patients during or after administration of ICIs, it is important to keep in mind that severe mucocutaneous disorders can occur regardless of the duration of the last dose [9,10] . In addition, dermatological treatments and skin care must be tailored to the patient's condition [5,11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, physicians must follow several general principles when confronted with these side effects. These principles are hit fast (experienced staff must evaluate patients from the beginning; in this regard, patients are issued brochures that briefly describe ICI treatment and can be handed to any emergency physician if needed), hit early (do not hesitate to initiate immunosuppression), hit strong (will escalate rapidly if needed), and hit short (will de-escalate treatment as soon as the patient is clinically and biologically suitable) [ 14 ].…”
Section: Reviewmentioning
confidence: 99%